Vertical distribution of sediment phosphorus in Lake Hachirogata related to the effect of land reclamation on phosphorus accumulation - Jin, G (Environmental technology, 2016)
The focus of this work is the change in sediment properties and chemical characteristics that occur after land reclamation projects. The results indicate a higher sedimentation rate in Lake Hachirogata after reclamation, with the rate increasing with proximity to the agricultural zone. In the west-side water samples, higher levels of dissolved total nitrogen and dissolved total phosphorus (DTP) were found in both surface and bottom waters. The increase in P (39-80%) was generally greater than that for N (12-16%), regarding the nutrient supply from reclaimed farmland in the western part of the lake. In the eastern part of the lake, the pore-water Cl- profile showed a decreasing vertical gradient in the sediment core. This indicates desalination of the lake water after construction of a sluice gate in 1961. In the western sediment-core sample, a uniform Cl- profile indicates the mixing of lake water and pore water after reclamation. Considering the sedimentation of P in the last 100 years, there is a trend of increasing accumulation of P and P-activities after the reclamation project. This appears to be an impact from change in the lake environment as a result of increased agricultural nutrients, desalination, and residence. A large amount of mobile phosphorus (42-72% of TP in the western core sample) trapped in sediment increases the risk of phosphorus release and intensification of algal blooms. High sediment phosphorus and phosphorus mobility should be considered a source of pollution in the coastal environment